Projeto Aldeia Cidadania: oficinas de leitura e escrita com jovens em uma organização não-governamental - Ferreira, Karin Terrell [UNESP] (2005)
This work was originate from reading and writing workshops developed into Aldeia-Movimento Pró-Cultura, a Non-Governmental Organization that attends young people that came from unfavorable social sectors in city of Limeira, in the State of São Paulo. The objective from reading and writing workshops were to glimpse the development of language, thought and relationship strategies of these young people and understand how they build their cognition, political and socialhistorical processes, as well as how these workshops would contribute to insert these young citizens into society. The hypothesis is that, once the word is the main way to constitute human being feelings, that leads them to a constant transformation of individual and public activities, when allowing these young boys and girls - mainly deprive of a practical contact with a text - a reading and writing work, it could contribute to build the subjectivity of these people, as well as contribute in the moment of intellectual appropriation of external objects, enlarging the building of their knowledge into a social way. It was searched into this work: 1) a discussion regarding the formation of a neoliberal State, trying to comprehends the transformation occurred to capitalist societies during this period and the marks under the influence of neoliberalism into Brazilian society and education; 2) research one of the models inside this new relationship between society and State, organization that is current outside the State formal structure: the Third Sector, specially Non-Governmental Organizations; 3) presentation of a historical description of the Non-Governmental Organization Aldeia Movimento Pró-Cultura, of Projeto Aldeia Cidadania and its reading and writing workshops to needy young people; 4) a study of the subjective moment into different processes and forms of organization when building the subjectivity into these... (Complet abstract, access undermentioned eletronic adress)